Big Money: The Effect of Money Size on Value Perceptions and Saving Motivation. (June 2016) - Peetz, Johanna; Soliman, Monica
Motivated perception has been shown to affect people's estimates of money (e.g., perceiving coins as larger than real size). In the present research, we examine whether simply varying the size of a picture of money can affect its perceived value and subsequent decisions. Participants presented with a picture of money enlarged by 15% perceived the depicted money as more valuable compared with those seeing a real-size picture (Study 1). When told to imagine their own cash and banked money in the depicted form, participants presented with a picture enlarged by 15% felt more subjectively wealthy and reported fewer intentions to conserve their money compared with those seeing a real-size picture of the same money (Study 2). Together, these studies suggest that judgments about money and even attitudes toward personal spending can be influenced by manipulating the size of a picture of money.